Nutritional analysis of vegetable soybean [Glycine max (L.) Merrill] accessions in Eastern India - Meghana, Devireddy; Rachana, Kodihalli Somashekar; Pan, Rabi Sankar; Kumar, Sandeep; Bishi, Sujit Kumar; Jawed, Danish; Mahatma, Mahesh Kumar; Kumari, Meenu; Shinde, Reshma; Sharma, Brij Bihari; Talukdar, Akshay; Kumar, Prakash; et al. (Frontiers in Nutrition, 2025)
IntroductionVegetable soybean (Glycine max L. Merrill), commonly consumed as edamame, represents a nutritionally dense crop with growing global demand. Despite its potential to address dietary diversification and enhance functional food markets, systematic evaluation of its biochemical traits remains limited, particularly in Eastern India where malnutrition and low crop diversity persist.MethodsThirty-four vegetable soybean genotypes were assessed under field conditions using a randomized block design with three replications. Quantitative analysis of proteins, carbohydrates, sugars, oil, fatty acids, vitamins, isoflavones, tocopherols, phenolics, trypsin inhibitor activity, and lipoxygenase activity was conducted using HPLC, GC, and spectrophotometric assays. Multivariate analyses including PCA, correlation, and hierarchical clustering were performed to identify trait associations and superior genotypes.ResultsSignificant differences (p ≤ 0.05) were observed among genotypes for all the parameters. Protein content varied between 25.7 and 34.9%, while sugars ranged from 13.5 to 24.6%. Our analysis showed that vegetable soybean genotypes, particularly AGS-190 and AGS-456, contained oleic acid levels exceeding 50%, which is considerably higher than those typically reported in grain soybean, thereby indicating improved oxidative stability. Isoflavone content was more than 14 mg/100 g in several accessions, whereas AGS-292 and AGS-610 recorded lower trypsin inhibitor and lipoxygenase activities, respectively, improving consumer suitability. Considerable diversity was also observed for tocopherols, phenolics, and vitamin C, indicating scope for enhancing antioxidant potential. Multivariate analyses identified a set of superior lines integrating multiple desirable traits, marking them as promising candidates for biofortification, functional food development, and breeding of next-generation vegetable soybean cultivars.DiscussionThe findings align with earlier studies reporting wide genotypic variation in protein, oil, sugar content and bioactive compounds of vegetable soybeans. However, unlike grain soybeans, the vegetable soybean genotypes showed higher oleic acid and lower linoleic acid, likely due to differences in harvest stage and seed maturity. Certain parameters showed ranges, comparatively lower than earlier studies, likely due to genotype-specific differences and agro-climatic conditions. These variations emphasize the need for region-specific screening to identify nutritionally rich and consumer-preferred cultivars.